Humour to humour: Laughing your mind open. - Meera Rada Krishnan, * (2013)
Humor is known to reduce students’ stress and enhance their learning experience (Steele 1998). The objective of this study is to explore the conduciveness of using self-disclosure, sharing sessions and humor in maintaining a safe, sharing environment within the classroom thus establishing trust and encouraging students to actively participate in the academic process. A survey to assess the effectiveness of humor and self-disclosure was administered to a sample of 143 pre-university students of year 2012 and 212 students of year 2013 from the Cambridge GCE ALevel (A-Level), Australian Matriculation (AUSMAT) and Monash University Foundation Year (MUFY) cohorts. 20 questions were posed using a 5 point Likert scale. The difference in the student’s responses based on the course undertaken was analyzed and the statistical significance of the differences was determined using standard error and t-tests (Seltman 2012). Results indicate that for the 2012 and 2013 cohorts, over 80 per cent and 78 per cent of the respective respondents agreed that the use of humor reduces students’ tension. Over 79 per cent and 81 per cent agree that a fun and open lecturer fosters a more positive learning environment thus enhancing attention, attendance, learning and retention. Over 75 per cent and 82 per cent agreed that self-disclosure encourages rapport and development of a sense of comfort thus increasing the approachability of lecturers. There appeared to be no significant difference between courses to the responses chosen. This study indicated that students did perceive humor and self-disclosure as an effective teaching tool. Therefore educators should seriously consider transforming lectures from being perceived as boring, difficult and stressful experiences into a positive learning environment.